Avaliação do potencial metanogênico em reatores em batelada tratando esgoto sintético em diferentes condições: biomassa de crescimento disperso e aderido - Lemos, Israel Silva (2019)
There are numerous technologies applied to remove organic matter with CH4 utilization of the process. Anaerobic digestion results as a byproduct called biogas, with methane having a majority share in this composition. In order to analyze methane production and organic matter removal in biological treatment system, a batch reactor was used through anaerobic digestion. Thus, this work aims to verify the performance of 4 reactors under different conditions: 2 reactors with 18.2 g COD.L-1, and 2 reactors with 30.8 g COD.L-1. For each concentration, the suspended biomass growth and the immobilized growth were performed by polyurethane foam under constant agitation at 120 rpm. The methodology applied for methane production analysis was the nonlinear Gompertz model, in order to adjust the curves from gas chromatography and allow the extraction of the maximum production points. Reactor operating time was 40 days. After this period it was possible to conclude that the 18.2 g DQO.L-1 reactor with immobilized biomass presented a more satisfactory performance, with 49.4% efficiency in the removal of organic matter and yield of 0.44 m³ CH4 / Kg. In contrast, the lowest result was for the 30.8 g COD suspended suspended biomass reactor, with 26.27% COD reduction and 0.40 m³ CH4 / Kg SV production.